Paradigma Aktualisasi Diri Anak Sejak Di Usia Dini (Analisis Pada Penerapan Di Lingkungan Pendidikan Anak Dalam Perspektif Pendidikan Islam) - Aryati, Ani (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Nature education is a responsibility shouldered the burden of someone, or a group on education due to something being performed, either because of the concepts or ideas, words and deeds or because it doesn't do anything. Islamic education is actually very completely in order to guarantee the outcome of a quality Islamic education because education in Islam is not only in view of the realization of humanitarian responsibility but it is a religious responsibility. Islamic education is the embodiment of the top education family, society and the Government are synergistic. Responsibility of the respective responsibilities of the institutions of Islam could be financing, energy, materials, ideas, information, creation of a conducive educational, infrastructure and education. Each is involved in education should BE responsible with the dipikulnya the slightest burden either vertical (habl min Allah) or horizontally (habl min al-nas).